Pengembangan Rumah Ikan untuk Mewujudkan Desa Sehat, Sejahtera dan Bebas Narkoba - Jafar La Kilo; Muhammad Taupik (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
Drug abuse will have a negative impact on a person's life or future, physically, psychologically and socially. Physically it will cause disturbances in the nervous system, disorders of the heart and blood vessels, skin disorders and disorders of the lungs. Psychologically, it causes sluggishness in work, often tense and anxious, loses confidence, becomes violent and has brutal behavior, has difficulty concentrating, tends to hurt oneself, feels insecure, and even commits suicide. The social impacts that may occur include mental disorders, anti-social and immoral, ostracized by the environment, troublesome and a burden on the family, disrupted education and a bleak future. Seeing the magnitude of the impact caused by drugs, a good and accurate solution is needed, especially in the coastal villages of Tomini Bay (including Tobango District). It takes strong resilience from the apparatus and village communities to tackle the drug problem. through the Development of the Anti-Drug Cadre Inspiration House (FISH) to Realize the Village's Sustainable Development Goals (SDGs) point 3, namely Healthy, Prosperous, and Drug-Free Villages.